ANALISIS NILAI TAMBAH DAUN KERSEN SEBAGAI BAHAN BAKU SIRUP PADA CV HARYO INDUSTRI KABUPATEN KENDAL - Istanto, Istanto; Prabowo, Rossi (Universitas Wahid Hasyim, 2021)
Abstrak Added value is the addition of the value of a product before the production process is carried out and after the production process is done. Processing of kersen leaves into kersen leaf syrup is done with the aim of increasing selling value. Through the activities of the production process, it is possible to provide added value as a result of the issuance of costs, resulting in higher new prices and greater profits.The purpose of this study is to find out how much value added from the processing of kersen leaves to syrup in the CV.HaryoIndustri home industry in Kendal Regency. The basic method of this research is descriptive method while the method of implementation is a case study technique that is in the home industry business of CV Haryo Industri in Kendal Regency. The number of respondents interviewed as many as 6 people consisted of business owners and labor. While collecting data and information with interview techniques, recording and observation.The results showed that the gross added value in the business of making leaf syrup in CV Haryo Industries Kendal Regency obtained a value of Rp. 177,210,000, net added value of Rp. 166,798,958, added value per syrup raw material is Rp. 402,750 / kg, and added value per workforce of Rp. 54,903 / JKO. While the total costs incurred by CV Haryo Industri in making syrup of kersen leaves in a one-year production period amounted to Rp. 214,561,042. These costs are obtained from the sum of the fixed costs of Rp. 38,281,042 with variable costs of Rp. 176,280,000. Whereas the amount of receipts for making syrup from the leaves of CV Haryo Industries during 2017 amounted to Rp. 277,830,000 / year with an income of Rp. 63,268,958 / year. Kata Kunci: Kersen, Value added, financial aspects